2019
DOI: 10.1039/c9ay00252a
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for the fast identification and monitoring of microplastics in environmental samples using random decision forest classifiers

Abstract: A new yet little understood threat to our ecosystems is microplastics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 26 publications
1
99
0
1
Order By: Relevance
“…Machine learning was also used to classify microplastics in spectral maps. Hufnagl et al 176 proposed a random forest approach to detect microplastics in mIR images as shown in Fig. 11.…”
Section: Machine Learning Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning was also used to classify microplastics in spectral maps. Hufnagl et al 176 proposed a random forest approach to detect microplastics in mIR images as shown in Fig. 11.…”
Section: Machine Learning Applicationsmentioning
confidence: 99%
“…Hufnagl et al 176 claim that the algorithm (a) (b) (c) (d) Figure 11. Microplastic classification in mIR images using a machine learning approach introduced by Hufnagl et al 176 The images from left to the right represent a zoomed-in and panned view of a sample: (a) optical image of the microplastic sample, (b) mIR image, (c) pixelwise classification output of the machine learning model for the different polymer types (including PE, PP, PMMA, PAN, PS, and nonpolymer particles), and (d) overlay of the classification result with the optical image of the sample. Reproduced from Hufnagl et al 176 with permission from The Royal Society of Chemistry.…”
Section: Machine Learning Applicationsmentioning
confidence: 99%
“…This identification is quick and allows the user to judge the interpretations made by the machine. The KNN method applied to IR spectra could also be applied to data obtained using automated methods such as focal plane array (FPA) detector combined with BaF2 window or, with another learning database, to data from Raman spectrometry (Cabernard et al, 2018;Hufnagl et al, 2019;Primpke et al, 2019). Raman spectrometry is indeed often used for the analysis of microplastics and is likely to provide additional information (Frère et al, 2017;Hahn et al, 1997;Hiejima et al, 2018;Zhao et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In 2018, an automated identification method based on hierarchical cluster analysis was published (Primpke et al, 2018). More recently a new method based on Random Decision Forest was proposed (Hufnagl et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation